Learning to live with datafication educational case studies and initiatives from across the world - Pangrazio, Luci; Sefton-Green, Julian (Routledge, 2022)
"As digital technologies play a key role across all aspects of our societies and in everyday life, teaching students about data is becoming increasingly important in schools and universities around the world. Bringing together international case studies of innovative responses to datafication, this book sets an agenda for how teachers, students and policy makers can best understand what kind of educational intervention works and why. Learning to Live with Datafication is unique in its focus on educational responses to datafication as well as critical analysis. Through case studies grounded in empirical research and practice, the book explores the dimensions of datafication from diverse perspectives that bring in a range of cultural aspects. It examines how educators conceptualise the social implications of datafication and what is at stake for learners and citizens as educational institutions try to define what datafication will mean for the next generation. Written by international leaders in this emerging field, this book will be of interest to teacher educators, researchers and post graduate students in education who have an interest in datafication and data literacies"
Keywords: Education -- Data processing -- Case studies; Internet literacy -- Case studies; Information resources management -- Case studies; Informationskompetenz; Medienkompetenz; Pädagogik; Datenkompetenz; Bildung; Digitalisierung; Fallstudiensammlung